Environmental and food security implications of livestock abortions and calf mortality: a case study in Kenya and Tanzania - Gurmu, Endale B.; Bronsvoort, B.; Cook, Elizabeth A.J.; Lankester, F.; Özkan, Ş.; Rosenstein, P.K.; Semango, G.; Wheelhouse, N.; Wilkes, A.; Arndt, Claudia (Frontiers Media, 2024)
This study investigates the environmental and food security implications of livestock abortions and calf mortality in Tanzanian dairy systems and Kenyan beef systems by utilizing data from previously published studies. The environmental impact of livestock abortion is assessed in Tanzanian dairy systems, examining indigenous and exotic breeds of cattle and goats in Northern Tanzania. Calf mortality’s impact is evaluated in Kenyan beef systems, involving local cattle breeds in western Kenya. Greenhouse gas (GHG) emission intensity (EI) is estimated for both countries. The GHG emissions in Tanzania consider enteric fermentation, manure management, and feed production in different cattle and goat groups, as well as total milk production. In Kenya, enteric methane (CH4) EI related to calf mortality is assessed by estimating lifetime enteric CH4 emissions and total carcass production from dams and their offspring. The EI is compared between the observed scenario (16% calf mortality) and alternative scenarios (8, 4, and 0% calf mortality). A life cycle assessment using the Global Livestock Environmental Assessment Model-interactive (GLEAM-i) examines GHG sources and potential tradeoffs. Estimates are made for milk and carcass losses due to abortions and calf mortality, scaled to represent the entire country. Abortion increases milk EI by 4–18% in Tanzania, while Kenya’s EI ranges from 25.9 to 27.6 kg CO2 eq per kg carcass weight. Animal protein loss due to abortions is equivalent to the potential annual animal protein requirements of approximately 649 thousand people in Tanzania, while a 16% calf mortality rate in Kenya is equivalent to per capita consumption of 4.5 million people. The findings highlight the significant impact of abortions and calf mortality on GHG emissions and animal protein availability, emphasizing the potential for reduced emissions and improved food security through mitigation efforts. The contribution of emissions from enteric fermentation and manure management is significant across both countries, underscoring the importance of a systems perspective in evaluating the environmental impact of livestock production. This study provides insights into the environmental and food security implications of livestock abortions and calf mortality in Tanzania and Kenya, emphasizing the need for targeted interventions in sustainable livestock production.